Comparison of genotypic and phenotypic antimicrobial profile in carbapenemases producing Klebsiella pneumoniae : The adoption of rapid antimicrobial susceptibility testing to improve patient’s outcomes - Del Rio, Arcadia; Puci, Mariangela; Muresu, Narcisa; Sechi, Illari; Saderi, Laura; Cugia, Luigi; Sotgiu, Giovanni; Piana, Andrea (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Prompt administration of appropriate antibiotic therapy is crucial in improving outcomes, particularly in cases sustained by multi-drug resistant strains. Although phenotypic antimicrobial susceptibility testing (AST) represents the gold standard to address antibiotics treatment, the long time required to obtained affordable results could negatively affect the prognosis. In contrast, rapid genotypic AST provide essential information for treatment and surveillance program. In order to evaluate the potential adoption of rapid AST in clinical routine, we compared the genotypic and phenotypic antimicrobial profiles of different K.pneumoniae strains, characterized by different expression of carbapenemases-encoding genes. Methods: A set of 109 strains of Cr-Kp were tested for the antimicrobial drugs by the automatized Vitek II system and, in parallel, to the new combination of β-lactams/β-lactamases inhibitors (BL/BLI) by Etest. An antimicrobial resistance index (ARI) was calculated for each strain, assigning each 1 or 0 points based on observed resistance/susceptibility, and dividing the total by the number of antibiotics tested. Kruskal-Wallis test, followed by Dunn’s post hoc test (Bonferroni correction), were used to compare quantitative variables among resistance gene subgroups. Results: We observed a higher ARI score in KPC/OXA-48 strains, similar profile in KPC alone and KPC/CTX-M groups and a significant lower resistance in no-carbapenemases-producing group. Same trend was observed in AST for BL/BLI. Conclusions: These preliminary results showed a close link between genotypic and phenotypic AST, supporting the adoption of rapid AST in cases of severe infections, ensuring to saving time and providing, the surveillance of MDR strains and improving stewardship programs.